ER stress promoted MAMs formation and ER-Mito Ca2+ transfer: implication for fluoride-induced hippocampal neuronal injury and cognitive deficits in mice - Siman Lin; LuYang Cao; Yuzhe Zhou; Shengdan Liu; Yue Yan; Qiwei Zhang; Quan Yuan; Yufei Gao; Ge Du; Jun Hu; Dongmei Wang; Hua Fan (Chemico-Biological Interactions, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Designing and the Pilot Trial of Bivalve Molluscan Fishing Quotas on Maoming Coastal Waters of China, Northern South China Sea - Shaoliang Lyu; Siman Deng; Kun Lin; Jiawei Zeng; Xuefeng Wang (Frontiers in Marine Science, 2022)
In the context of the declining fishery resources, some active management measures have been taken to strive for the sustainable development of fisheries. However, these input-oriented control management measures have not realized the expectation in alleviating the depressing depletion of fishery resources. The fishing quota (FQ) system, an output-oriented control management method, has been proved to be effective in curbing overfishing and conserving fishery resources. However, it has not been formally implemented in China until now. Thus, it is urgent to start the pilot trial on the implementation of the FQ system in China. We firstly formulated a framework for the FQ system on bivalve fisheries and then conducted an empirical analysis based on the field survey of bivalve mollusks in Maoming shallow waters, Guangdong, northern South China Sea. The species composition, dominant species, and density distribution of bivalves were analyzed. The swept-area method was used to assess the total allowable catch (TAC) of bivalves. Each step of the FQ system was discussed in depth. Results showed that a total of 45 bivalve species were identified. Meretrix planisulcata and Ruditapes philippinarum were the two dominant species. The spatial distribution of density varied largely. The estimated TAC value is 4.28 × 10 5 kg which can be allocated to fishermen under the regulations of the FQ system. Finally, the framework for the FQ system was improved in every step of the future procedure, including target species selection, TAC determination, quota allocation, catch report, and fishing supervision. The general framework of the FQ system in this study can also be referenced to other economically important fish or other marine organisms.